Evolutionarily distinct lineages of a migratory bird of prey show divergent responses to climate change - Ferrer Obiol, Joan; Bounas, Anastasios; Brambilla, Mattia; Lombardo, Gianluca; Secomandi, Simona; Paris, Josephine R.; Iannucci, Alessio; Whiting, James R.; Formenti, Giulio; Bonisoli-Alquati, Andrea; Ficetola, Gentile Francesco; Galimberti, Andrea; et al. (Nature Communications, 2025)
Accurately predicting species’ responses to anthropogenic climate change is hampered by limited knowledge of their spatiotemporal ecological and evolutionary dynamics. We combine landscape genomics, demographic reconstructions, and species distribution models to assess the eco-evolutionary responses to past climate fluctuations and to future climate of an Afro-Palaearctic migratory raptor, the lesser kestrel (Falco naumanni). We uncover two evolutionarily and ecologically distinct lineages (European and Asian), whose demographic history, evolutionary divergence, and historical distribution range were profoundly shaped by past climatic fluctuations. Using future climate projections, we find that the Asian lineage is at higher risk of range contraction, increased migration distance, climate maladaptation, and consequently greater extinction risk than the European lineage. Our results emphasise the importance of providing historical context as a baseline for understanding species’ responses to contemporary climate change, and illustrate how incorporating intraspecific genetic variation improves the ecological realism of climate change vulnerability assessments.